Methodological foundations of the study anti-crisis economic transformations - Zadorozhnaya , O. G. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2018)
The article deals with the methodological principles of the research of anti-crisis economic transformations in the format of post-classical economic science. It is revealed that such a format involves determining the leading role of spiritual values in economic transformations. A transition to an understanding of the value rationality that fosters the goals of economic reforms is needed in order to increase the well-being of the Ukrainian people.The main three of the new methodological foundations of such a study are the understanding of a single tri-hypostasis - the spiritually-bio-social nature of man, the archetype of "freedom-responsibility" and the hypothesis of the unity of mankind, which steers all the good livelihoods of man as a special living species - homo sapiens. At the same time, a person manifests himself holistic only when the spiritual hypostasis sets forth the qualities, abilities and internal motives of the person which are to be deployed in the process of the integral economic life of each person.The need to create a new strategy for national economic development in order to increase the well-being of the Ukrainian people indicates that its foundation should be based on spiritual and moral values. Domestic science began to develop a new paradigm - spiritual-noospheric-sustainable development, the understanding of which makes it possible to unify the intrinsic aspects of the concepts of the noosphere and sustainable development and the theory of three-polar - spiritual and bio-social nature of man.The main vectors of the field of the new economic strategy are revealed: spiritual-moral and ethical-moral; bio-genetic-healing; socio-partner-co-evolutionary. The main methodological postulate in developing the national anti-crisis strategy of revival is the rising value-rational orientation when planning and implementing economic productive transformations in terms of creating the conditions for self-study and self-realization of human-personality.